2017
DOI: 10.1007/s10661-017-6208-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long exposure to spent potliner on seeds, root tips, and meristematic cells of Allium cepa L.

Abstract: Spent potliner (SPL) is a solid waste generated in the aluminum mining and processing industry. It is sometimes dumped into the environment and leach in contact with water, thereupon affecting living beings, which are likely to be exposed to the waste for long periods. Considering this, we aimed to evaluate the effects of extended exposure to SPL through bioassays using Allium cepa as plant model system. Seeds of A. cepa were either directly exposed to SPL (continuous exposure) or first germinated in water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Agents that reduce mitotic index have a tendency to also increase the frequency of condensed nuclei [25,26]. This was observed in the current study where the presence of condensed nuclei was observed on the tested dosages of 30 and 60 mg L -1 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Agents that reduce mitotic index have a tendency to also increase the frequency of condensed nuclei [25,26]. This was observed in the current study where the presence of condensed nuclei was observed on the tested dosages of 30 and 60 mg L -1 .…”
Section: Discussionsupporting
confidence: 83%
“…Root length is a parameter that relates with the rate of cell division and the mitotic index indicates this rate of division [25]. On the present work this relation was very evident, during the cytogenetic analysis it was observed that the herbicide interfered on the mitotic index and that was expected once you consider that the active ingredient tested also provoked a reduction on root and shoot growth as well as on the seedling as a whole.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Thus, a reduction in MI relative to the control indicates that differences are derived from the chemical effect of the substance, which results in the inhibition of the growth and development of the organism (Leme and Marin-Morales 2009 ). Mito-depressive effects have already been reported regarding the reduced elongation of A. cepa roots exposed to the herbicide imazethapyr (Liman et al 2015 ), metals (Gupta et al 2018 ), and mining waste (Andrade-Vieira et al, 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…Untreated SCC causes pollution of surface water and groundwater when it be landfilled or piled up in the open air. SCC threatens the health of animal and plant seriously, and ecological balance. As a worldwide concern about the environmental problem, spent cathode carbon has been classified as a hazardous solid waste in many countries and there are particular requirements in SCC treatment, storage, and transportation.…”
Section: Introductionmentioning
confidence: 99%